Absurdity as One of the Facets of Law in Russia - Zakhartsev, Sergey I. (Opción, 2019)
This article presents a scientific discussion about such a facet of law as absurdity and outright stupidity of certain legal norms via a complex of philosophical, semiotic, general scientific, theoretical and legal approaches, research principles and special techniques. In result, Law and ideas about law may appear very different matters for a particular person. So, the conclusions and decisions these people make can hardly be called anything else but absurdity and legal nonsense. In conclusion, meaningless, useless and frankly stupid norms exist in many (if not in each) branches of law. Rationality is the antonym of stupidity.